Education, globalization, and citizenship: reflections of Vietnamese local school teachers and overseas-educated academics. Issue 5 (3rd September 2021) - Pham, Lien; Duong, Bich-Hang
ABSTRACT: Drawing on two research projects that include Vietnamese overseas-educated academics and local school teachers, the paper discusses these educators' reflections on citizenship, citizenship education and Vietnam's higher education reform in the context of globalization. Through the lens of Michel Foucault's knowledge/power and subjectivity, and taking on Arjun Appadurai's social imaginary, we illustrate the contested values of education and complex meanings of citizenship in a market-based economy with socialist ideologies, and their effects on educators' practices.